Magnetic contrast at spin-flip excitations: an advanced x-ray spectroscopy tool to study magnetic-ordering - Elnaggar, Hebatalla; Haverkort, Maurits W. (ACS applied materials & interfaces, 2019)
The determination of the local orientation and magnitude of the magnetization in spin textures plays a pivotal role in understanding and harnessing magnetic properties for technological applications. Here, we show that by employing the polarization dependence of resonant inelastic X-ray scattering (RIXS), we can directly probe the spin ordering with chemical and site selectivity. Applied on the prototypical ferrimagnetic mixed-valence system, magnetite ([Fe3+]A[Fe3+,Fe2+]BO4), we can distinguish spin-flip excitations at the A and B antiferromagnetically coupled Fe3+ sublattices and quantify the exchange field. Furthermore, it is possible to determine the orbital contribution to the magnetic moment from detailed angular dependence measurements. RIXS dichroism measurements performed at spin-flip excitations with nanometer spatial resolution will offer a powerful mapping contrast suitable for the characterization of magnetic ordering at interfaces and engineered spin textures.
Gesehen am 28.01.2020